SYNTACTICAL ERROR ANALYSIS ON REPORT TEXT - Soraya Grabiella Dinamika; Ridwan Hanafiah (JOALL (Journal of Applied Linguistics and Literature), 2019)
This study aims at investigating and classifying the syntactical errors in the writing of report text made by 20 students of Department of English Literature of FIB-USU. Syntactical errors in writing made by EFL students are needed to be investigated by using the Error Analysis theory developed by Gass & Selinker in 2008 as it provides six appropriate investigation procedures, namely; collecting data, identifying errors, classifying errors, quantifying errors, analyzing errors and remediation.  Each of students was assigned to write a topic-based report text with the length of 150 up to 250 words in count. This study dealt with a qualitative descriptive approach. After the EA procedures applied, in this study found that the students made major syntactical errors within the use of article ‘a/an’,’ the’ in terms of omission and addition of articles, the use of relative pronoun, and the use of subject-verb agreement in terms of past tense agreement and number agreement. Based on the error analysis procedure applied, it was obtained that the most predominant syntactical errors made by the students was the use of article which comprises of 125 errors (50.2%), followed by the use of subject-verb agreement with 117 errors (47%) and followed by the use of relative pronoun as the least error which comprises of 7 errors (2.8%). The syntactical error made by the students caused by two major sources, intra-language error and intra-language error. By seeing at these problematic areas, the researcher has suggested to take out several related pedagogical remediation to the students.